2020
DOI: 10.1104/pp.19.01485
|View full text |Cite
|
Sign up to set email alerts
|

Communication between the Plasma Membrane and Tonoplast Is an Emergent Property of Ion Transport

Abstract: Dear Editor, A very substantial body of data now exists for ion transport at both the plasma membrane and the tonoplast of several plant cell models, notably for guard cells, root hairs, and epidermal cells of several species to name a few (Grierson et al., 2014; Jezek and Blatt, 2017; Wang et al., 2019). This knowledge has its foundation in detailed electrophysiological and flux studies that have provided quantitative biophysical and kinetic information. Our understanding has expanded through molecular biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In the cellular context, however, these membranes are not isolated. Instead they communicate with each other via the cytosolic concentrations (Vincent et al, 2017; Horaruang et al, 2020). Previous studies have shown that membrane sandwiches exhibit another level of dynamics (Gajdanowicz et al, 2011; Schott et al, 2016; Dreyer et al, 2017; Dreyer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the cellular context, however, these membranes are not isolated. Instead they communicate with each other via the cytosolic concentrations (Vincent et al, 2017; Horaruang et al, 2020). Previous studies have shown that membrane sandwiches exhibit another level of dynamics (Gajdanowicz et al, 2011; Schott et al, 2016; Dreyer et al, 2017; Dreyer et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Such modifications can influence the different types of transport reactions across the different membranes involving ion i (Box 1). Thus, Δµ i , together with the kinetic properties of the ion transporters, affects ion fluxes across cellular membranes, and changes in cytosolic ion concentrations modify the movement of ions across the membranes facing the cytosol (Wang et al ., 2017; Horaruang et al ., 2020). Therefore, changes in the ionic conditions in the cytosol participate in the coordination of ion fluxes between cellular membranes (Fig.…”
Section: Ion Flux Coordination Under the Control Of Ionic Conditions mentioning
confidence: 99%
“…There are many predictions that can be drawn from OnGuard2 simulations, a number of which have been validated experimentally. Of these, OnGuard2 models of Arabidopsis have accurately predicted the transient stimulation of inward-rectifying K + channels on recovery from steps in ambient %RH, an acceleration in the recovery of stomatal conductance with %RH [ 8 ], and co-ordinated alterations in osmotic solute transport across the tonoplast and its retention in the slac1 mutant [ 8 , 66 ]. Similarly, the OnGuard platform predicted, as a target for enhancing stomatal gas exchange and water use efficiency (defined as the amount of carbon fixed in photosynthesis divided by the amount of water lost via stomatal transpiration), the importance of introducing new channel gating behaviours over simple increases in the populations of channels and pumps at the guard cell plasma membrane [ 67 ].…”
Section: Interrogating Onguard Platform Outputsmentioning
confidence: 99%